PRESUPPOSITION ON ENGLISH SLOGAN OF FOOD AND BEVERAGE SLOGAN ADVERTISEMENT IN TELEVISION (PRAGMATICS APPROACH) - MARYATUN , RIRIEN (2010)
This research paper analyzes the presupposition meaning on English slogan of food advertisements applying semantic approach. There are two problem statements raised in this research paper; 1) What are the presupposed meanings behind the English food and beverage advertisement slogan in television? and 2) What are types of the presupposition meaning of the English food and beverage advertisement slogan in television? The data sources of this research are the English food advertisements shown in the television. The data are in the form of phrases and sentences. There are 26 (twenty six) data gathered for this research. In gathering the data, the researcher uses descriptive qualitative method. The result of the research paper are; 1) The literal meaning and presupposed meaning of food and beverage advertisement products is different. It is because the advertisers want to send particular message in the advertisement. It is relevant to the notion that presupposition allows people the freedom not to make everything absolutely explicit in our communications, and 2) The common food and beverage advertisement slogan is in the form of implicative presupposition (15 data or 57,6%), while only 11 data (42,3%) are change-of-state presupposition.